Implications of Information Technology Advances on the Development of Students' Islamic Boarding School Learning Process - Rizki, Muhammad (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The goal of this study is to examine how the advancement of information technology has influenced the development of the students learning process in Islamic boarding schools. This type of research employs a descriptive qualitative approach, with a focus on education. The population consists of 189 students who are the subjects of this research. The sample for this study consisted of two students from the supervisor or lecturer at Ma'had 'Aly As'adiyah Sengkang, one of the 11 students. The sampling process used a purposive sample technique. The instruments used to obtain data include observation sheets, interview guidelines, and questionnaires. The data analysis employed a descriptive qualitative approach, incorporating inductive, deductive, and comparative methods. The findings of the study indicated that the implications of advances in information technology on the learning process at Ma'had Aly As'adiyah Sengkang have positive and negative impacts. The positive impact obtained from advances in information technology is the ease of obtaining information and communicating, all of which are very helpful for the development of the learning process both for students and for lecturers as educators. The negative impacts that will arise from information technology depend on the user of the information technology itself; some students also know the limitations of the use of information technology.